Influence of N-Acetyl-L-Cysteine on the Pharmacokinetics and Antibacterial Activity of Marbofloxacin in Chickens - Albena Roydeva; Nikolina Rusenova; Aneliya Milanova (Antibiotics)
Background/Objectives: Marbofloxacin, a second-generation fluoroquinolone, is used to control economically significant poultry diseases caused by pathogenic bacteria such as Staphylococcus aureus and Escherichia coli. Although synergistic antimicrobial activity between fluoroquinolones and N-acetyl-L-cysteine (NAC) has been observed in vitro, data on their pharmacokinetic interactions in vivo remain limited. This study aimed to evaluate the effect of NAC on the oral pharmacokinetics of marbofloxacin in broiler chickens and its antibacterial activity against E. coli ATCC 25922 and S. aureus ATCC 25923, assessing the potential benefits of their combined administration. Methods: The pharmacokinetics of marbofloxacin was evaluated in broilers (5 mg/kg dose) after a single intravenous (n = 12) or single oral (n = 12) administration into the crop. The protocol for the co-administration of marbofloxacin and NAC (400 mg/kg via feed) was as follows: on the first day, the poultry (n = 12) received a single oral dose of marbofloxacin via the crop and over the next four days the fluoroquinolone drug was administered via their drinking water. The plasma levels of the drugs were determined using LC-MS/MS analyses, and minimum inhibitory concentrations were determined using the microbroth dilution method. Results: NAC significantly reduced the bioavailability of marbofloxacin after a single oral administration into the crop and decreased the elimination rate constant following the administration of both drugs. At a concentration of 20 μg/mL, NAC led to a 3.8-fold reduction in the MIC of marbofloxacin against E. coli ATCC 25922 and a 2-fold decrease at concentrations between 1 μg/mL and 6 μg/mL, while no change was observed in marbofloxacin’s effect on S. aureus ATCC 25923. Conclusions: Oral co-administration of NAC and marbofloxacin reduced the fluoroquinolone’s bioavailability by two-fold while enhancing its antibacterial activity against E. coli ATCC 25922.